Biologic therapies for systemic lupus erythematosus: where are we now?. Issue 6 (November 2020) - Murphy, Grainne; Isenberg, David A.
Abstract : Purpose of review: Conventional approaches using hydroxychloroquine, corticosteroids and immunosuppressives have improved the prognosis for systemic lupus erythematosus (SLE) patients. Unfortunately, they have reached the limits of what they can achieve and patients still die prematurely and/or find their quality of life greatly impaired. Here, we discuss the problems of assessing activity in SLE, optimizing clinical trial design and more recent biologic approaches. Recent findings: The success of B-cell depletion using Rituximab in open clinical studies, the approval of Belimumab (blocks the B-cell activating factor BAFF) and improvements in clinical trial design, gives cause for hope. Approaches including the use of fully humanized anti-CD20 and CD19 monoclonals, blocking interferons, inhibiting Bruton's tyrosine kinase (BTK), blocking the CD40 ligand (CD40L), utilizing an analogue of the Fc[Latin Small Letter Gamma]RIIB and an IL12-23 blocker and targeting the JAK-STAT pathway have met end points in phase II and III trials. Summary: For 20 years, we hoped that the successes of the biologic therapies in rheumatoid arthritis and psoriatic arthritis would be replicated in SLE but we have been generally disappointed. However, the encouraging recent results with monoclonals that block interferon and fully humanized anti-CD20 in particular, offer the prospect of a real revolution in the treatment of SLE.